2020
DOI: 10.3390/ma13040835
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Effect of Thermal Treatment on the Obtaining of Magnetic Phases: Fe5Y, Fe23B6, Y2Fe14B and αFe within the Amorphous Matrix of Rapidly-Quenched Fe61+xCo10−xW1Y8B20 Alloys (Where x = 0, 1 or 2)

Abstract: The paper presents the results of research on the structure and magnetic properties of Fe61+xCo10−xW1Y8B20 alloys (where x = 0, 1 or 2). The alloys were produced using two production methods with similar cooling rates: Injection casting and suction casting. The alloy samples produced were subjected to isothermal annealing at 940 K for 10 min. The structure of the materials was examined using X-ray diffraction. Isothermal annealing has led to the formation of various crystallization products depending on the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This means that privileged system clusters are much easier to form in four-component systems. In numerous studies [28] of alloys with the addition of Y (FeCoYB), it has been demonstrated that one of the most frequently formed crystalline phases is magnetically soft phase αFe, magnetically semi-hard phase Fe 5 Y, and magnetically hard phase Y 2 Fe 14 B. In the case of the FeNbYB alloy, an axial shape of the hysteresis loop was observed, indicating the appearance of a magnetic phase in the alloys with hard or semi hard magnetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…This means that privileged system clusters are much easier to form in four-component systems. In numerous studies [28] of alloys with the addition of Y (FeCoYB), it has been demonstrated that one of the most frequently formed crystalline phases is magnetically soft phase αFe, magnetically semi-hard phase Fe 5 Y, and magnetically hard phase Y 2 Fe 14 B. In the case of the FeNbYB alloy, an axial shape of the hysteresis loop was observed, indicating the appearance of a magnetic phase in the alloys with hard or semi hard magnetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the cooling rate and chemical composition, it is possible to produce alloys with an amorphous or nanocrystalline structure in a one-stage process [1]. The type of phases formed during solidification determines the properties of these materials -rapid quenched alloys may have hard magnetic properties (for example, with the Y 2 Fe 14 B phase [2]), semi-hard magnetic properties (with the Fe 5 Y phase [3]), or soft magnetic properties (with the α-Fe, Fe 2 B, Fe 23 B 6 , Fe 3 B [4][5][6]). The properties of these alloys are related, among other things, to the distances between magnetic atoms [7] and the size of crystal grains [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are mainly four types of intermetallic compounds in M-B systems (M = Fe, Co, Ni): MB, M 2 B, M 3 B, and M 23 B 6 , whose formations are dependent on the solidification routes [13,14], which are affected by the composition and technology parameters, such as the cooling rate, the undercooling, the holding time, etc., and which show different magnetic properties because of the different contents of boron. It is worth noting that the Co 23 B 6 metastable phase is usually regarded as a good candidate for enhancing the soft properties [15], and, in addition, the Co 2 B phase with the higher boron content has an intrinsic hardness of about 816 HV, which is comparable to the hard chromium (860 HV). Its high hardness makes it a potential wear-resisting protective coating [16].…”
Section: Introductionmentioning
confidence: 99%